EVALUASI KRITERIA KESESUAIAN SISTEM PERKEBUNAN KARET DI DAERAH KERINCI DAN SEKITARNYA EVALUATION OF SUITABILITY CRITERIA FOR THE RUBBER PLANTATION SYSTEM IN KERINCI AND ITS SURROUNDING AREA - Nasrul, Besri; , Sudarsono; Ardiansyah, M. (Pembangunan Pedesaan, 2005)
Identification of land characteristics to evaluate the rubber plantation system was carried out at the Kerinci and its surrounding area, Riau from May 2002 up to October 2003. The objectives of this research were to identify land characteristics of plantation system influencing its production and benefit value, and to compile criteria of site specific. Location was identified by the Land-sat 7 ETM+ band 347 RGB designed in the land use utilization type (LUT): garden and estate. In each LUT it was done by measurement of land characteristics, cost the inputs, and price the benefits. The land characteristics were evaluated by parametric method; the benefit value was calculated by benefit-cost ratio (BCR); the suitability criteria of site specific were compiled by cluster analysis. The results showed that the production suitability criteria were (kg wet rubber/ha/yr): I (2,062.28-2,099.56); II (1,523.44-2,062.28); III (996.88-1,523.44); IV (933.13-996.88), the economic suitability criteria were (BCR): I (2.44-2.58); II (1.83-2.44); III (1.51-1.83); IV (1.32-1.51), and would be determined by drainage, base saturation, exchangeable Al, and organic-C. These criteria could be used for evaluating suitability of the rubber plantation system at the Kerinci and its surrounding area.